Measuring Options for Customary Land Registration From the Perspective of East Nusa Tenggara Findings - Chamdani, Muchammad Chanif (Arena Hukum, 2024)
This article identifies various options for administering the lands of customary law communities (MHA) that have been implemented or are enshrined in laws and regulations regarding the land sector in Indonesia and sees in what cases specific administration options can be implemented and what the possible challenges are. This research refers to secondary data from findings from the Inventory and Identification of Customary Land in 2021, especially in the province of East Nusa Tenggara. The research also uses a normative approach by examining laws and regulations regarding MHA land registration in the land sector. Based on rules and regulations in the land sector in Indonesia, there are several options for administering MHA lands, namely delineation of land parcels, registration of property rights, registration of communal rights, registration in the land register, and registration in the land management rights (HPL).